Arti Penting Pendidikan Anti Korupsi dalam Pembentukan Karakter dalam Pencegahan dan Pemberantasan Tindak Pidana Korupsi - Deddy Hendarwan (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2023)
Corruption is a crime that is categorized as a crime or an extraordinary crime, because the impact caused by this crime is very broad. In addition to harming state finances, this crime of corruption also harms the public, both directly and indirectly. These impacts have a major effect on the impact of Economy, Social and Poverty, Collapse of Government Authority, Politics and Democracy, Law Enforcement, Defense and Security, Environmental Damage, Cultural Defense and Religiosity. The impact caused by corruption, forms of corruption and anything related to criminal acts of corruption, so that students can understand about corruption, and the most important thing is to develop an Anti Corruption attitude or character. This is expected to be implemented through anti-corruption values ​​in everyday life. So that students as the next generation of the nation, as potential leaders of the nation can avoid various kinds of corruption. And from all students, we hope that the leaders of this nation will grow who have the character of anti corruption, noble character, become a model, a driver of national morality, will remain consistent in carrying out anti-corruption values ​​in the life of the nation.